Physical examination of the shoulder - Antoniou, John; Delaney, J. Scott; MEMmedia (Firm) (Berne, Switzerland : MEM Media, 2001)
(Producer) Discusses the anatomy, physical examination, and mechanisms of injury common in various shoulder injuries and complaints
Keywords: Shoulder Joint -- injuries; Physical Examination -- methods